New and Confirmed Combinations of New World Bruchinae (Coleoptera: Chrysomelidae) with a List of incertae sedis Species - Morse, Geoffrey E.; Ribeiro-Costa, Cibele Stramare (Zootaxa, 2024)
We identify 94 species of New World Bruchinae (Coleoptera: Chrysomelidae) that have not been revised since original publications that predate the establishment of current bruchine genera. Many of these have appeared in catalogs or checklists and have been transferred to genera without inspection of primary type specimens. We were able to inspect the primary types of 77 of these species; we provide new combinations for 38 and confirm previous combinations made in catalogs for an addition 39. We provide emended names for four taxa and designate a neotype for Bruchus atrosignatus Pic, 1935. Type specimens could not be located for 14 of the additional 17 species, with only three species of known deposition not yet inspected. These 17 species should be considered as species incertae sedis and included as such in any catalogs or checklists until types are examined by future reviewers.